PELATIHAN (WORKSHOP) PEMANFAATAN LIMBAH KAIN MENJADI ORNAMEN DEKORASI LIVING ROOM DAN DINING ROOM RUMAH TINGGAL - Ulinata; Luky Wirawan; Lintang Bagas Hartadi; Juan Vito (Jurnal Pendekar Nusantara, 2023)
Lecturers and students of Architecture Study Program Universitas Kristen Indonesia collaborations with partners Antheia and Fempire continued their Community Service activities entitled Training (Workshop) on Utilizing Fabric Waste to Make Ornaments Decorating Living Rooms and Dining Rooms for Residential Homes by presenting two speakers who are experts in their fields. The method is by preparing tools and materials to be used during the activity, coordinating with Antheia and Fempire partners so that the partners can become contact persons for the participants so that the participants can attend the activities which are planned to take place in two days on Harapan Island, precisely at the Antheia Production House. Label where the participants are housewives on Harapan Island with the hope that women's empowerment in the area can increase, then providing material provision first by the two speakers for further practice based on the material presented to the participants so that the extent of the participants' understanding regarding the material is known. be delivered. As a result, the participants succeeded in completing their products, including tablecloths for the living room, placemats and glasses for dining room ornaments from waste cloth. It is hoped that with this Community Service activity, the volume of fabric waste will slowly decrease, the participants will be able to make living room and dining room interior decoration elements using fabric waste but still look aesthetically pleasing and women's empowerment can be further increased, especially on Harapan Island.